Nonequilibrium-DMFT based RIXS investigation of the two-orbital Hubbard model - Werner, Philipp; Johnston, Steven; Eckstein, Martin (EPL - Europhysics Letters, 2021)
Resonant inelastic X-ray scattering (RIXS) detects various types of high- and low-energy elementary excitations in correlated solids, and this tool will play an increasingly important role in investigations of time-dependent phenomena in photo-excited systems. While theoretical frameworks for the computation of equilibrium RIXS spectra are well established, the development of appropriate methods for nonequilibrium simulations is an active research field. Here, we apply a recently developed nonequilibrium dynamical mean field theory (DMFT) based approach to compute the RIXS response of photo-excited two-orbital Mott insulators. The results demonstrate the feasibility of multi-orbital nonequilibrium RIXS calculations and the sensitivity of the quasi-elastic fluorescence-like features and d-d excitation peaks on the nonequilibrium population of the Hubbard bands.
CRIS-Team Scopus Importer:2021-05-14